Cognitive Counseling Behavioral with Modeling The Figure of Dharmawangsa to Increase Verbal - Wati, Ida Ayu Widya; Suarni, I Ketut; Dharsana, I Ketut (Bisma The Journal of Counseling, 2017)
This research aims to know the influence of behavioral counselingModeling techniquesDharmawangsa figure to improve verbal through lesson study on grade XII HIGH SCHOOL Language Lab Undiksha.This type of research is Research experiment pseudo ("Quasi alphabets experiment"). The population of this research was a HIGH SCHOOL Language class XII students of the laboratory Undiksha. Sampling techniques using a purposive sampling so that the retrieved 6 students who have low verbal ability as a group of 6 persons and more experiments as a control group. The Data collected with verbal ability tests of verbal ability.Methods of analysisthe test used wasthe t-test.Results of the study indicate that there is the influence of cognitive behavioral counseling with techniques of modeling the figure against the verbal ability of Dharmawangsa through lesson study.